Effects of soft tissue grafting prior to orthodontic treatment on preventing gingival recession in dogs - Song, Young Woo (J Periodontal Implant Sci, 2020)
PURPOSE: This study was conducted to assess the efficacy of prophylactic gingival grafting in the mandibular anterior labial area for preventing orthodontically induced gingival recession. METHODS: Eight mongrel dogs received gingival graft surgery at the first (I1) and third (I3) mandibular incisors on both sides based on the following group allocation: AT group (autogenous connective tissue graft on I1), AT-control group (contralateral side in the AT group), CM group (xenogeneic cross-linked collagen matrix graft on I3) and CM-control group (contralateral side in the CM group). At 4 weeks after surgery, 6 incisors were splinted and proclined for 4 weeks, followed by 16 weeks of retention. At 24 weeks after surgery, casts were made and compared with those made before surgery, and radiographic and histomorphometric analyses were performed. RESULTS: Despite the proclination of the incisal tip (by approximately 3 mm), labial gingival recession did not occur. The labial gingiva was thicker in the AT group (1.85±0.50 mm vs. 1.76±0.45 mm, P>0.05) and CM group (1.90±0.33 mm vs. 1.79±0.20 mm, P>0.05) than in their respective control groups. CONCLUSIONS: The level of the labial gingival margin did not change following labial proclination of incisors in dogs. Both the AT and CM groups showed enhanced gingival thickness.